2009
DOI: 10.1128/cvi.00333-08
|View full text |Cite
|
Sign up to set email alerts
|

Flagellin-F1-V Fusion Protein Is an Effective Plague Vaccine in Mice and Two Species of Nonhuman Primates

Abstract: A number of studies have clearly demonstrated that flagellin is a potent adjuvant that promotes robust immune responses when it is given with a protein antigen. In view of the potential biological and practical benefits of a recombinant protein vaccine composed of a single fusion protein containing flagellin and antigen, we have evaluated the efficacy of a fusion protein composed of flagellin and two protective antigens of Yersinia pestis (F1 and V) in eliciting protection against respiratory challenge with Y.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(101 citation statements)
references
References 34 publications
3
92
0
4
Order By: Relevance
“…37,38,[40][41][42] The current data support the conclusion that the adjuvancy of flagellin is more dependent on TLR5 than the NLRC4 inflammasome. 32 However, they also suggested that deficiency in the NLRC4-mediated activity of flagellin might make it a better adjuvant for enhancing the antibody response.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…37,38,[40][41][42] The current data support the conclusion that the adjuvancy of flagellin is more dependent on TLR5 than the NLRC4 inflammasome. 32 However, they also suggested that deficiency in the NLRC4-mediated activity of flagellin might make it a better adjuvant for enhancing the antibody response.…”
Section: Discussionsupporting
confidence: 77%
“…Flagellin functions as an immunogen to induce strong immune response against itself and co-administered antigens. [16][17][18][37][38][39][40][41][42] Based on its biological properties, flagellin or flagellin-based fusion proteins are being developed as therapeutic agents or vaccines to treat infectious diseases, toxic exposures, and even cancer. [43][44][45][46][47] In recent years, studies have shown that the immune activities of flagellin, such as adjuvancy, are dependent on TLR5 recognition and the NLRC4 inflammasome.…”
Section: Discussionmentioning
confidence: 99%
“…116 As described above, as a consequence of the potent effects of flagellin on both the innate and adaptive limbs of the immune system, the protein has indeed been demonstrated to have potent adjuvantic effects in experimental vaccine constructs. [117][118][119][120][121][122] However, the safety profile of flagellin is yet to be unequivocally established. Of particular note, it has been observed that the administration of flagellin at doses comparable to or lower than that of bacterial LPS induces prominent local and systemic immune/inflammatory responses in vivo.…”
Section: Tlr5 Agonistic Flagellinmentioning
confidence: 99%
“…Flagellin-triggered responses exert various effects on different cells, tissues and organs; these responses vary greatly according to the dose, physiological condition of the cell, the animal used and the experimental setting. 15,17,26 However, the beneficial flagellinactivated responses for host defenses and the potential adverse effects of flagellin in different organs can be contradictory. Therefore, the flagellin-triggered pathophysiological responses should be explored further to provide a clearer understanding of the correlation between the pattern recognition receptors (PRRs)-flagellin interaction and its pathophysiological effects to enhance the application of recombinant flagellin as a prophylactic and therapeutic agent.…”
Section: Introductionmentioning
confidence: 99%